(untitled) (Indian Journal of Chemistry (IJC), 2025)
Poly (para- diphenylamine-co-ortho-aminophenol) copolymers were synthesized through oxidative polymerization with sodium dodecylsulphate as the emulsifying agent. The synthesized copolymer was characterized using UV- visible spectroscopy, FT-IR, XRD, SEM and TG-DTA and DSC. The UV-Vis shows the peak 273 nm is due to the π →π* transition which is related to the extent of conjugation between the adjacent phenylene rings in the polymeric chain. A broad peak that shows in the area of 3850cm −1 is due to hydrogen-bonded –OH and –NH 2 groups. Two main peaks between 1564 and 1484 cm −1 refer to the ring stretching vibrations of the quinoid and benzenoid rings respectively. The XRD studies confirm the polymer has semicrystalline nature. The SEM analysis of the copolymer exhibited cluster like arrangement on the rough surfaces and wide dispersion, without any regularity in shape. The TGA illustrate there exists three stages of weight loss. The polymer was found to be thermally stable till 518⁰C with the residual mass of 0.48%. The fluorescence spectroscopy data shows that synchronous scanning for both excitation and emission peaks at 399nm.